Perancangan Interior Restoran Crystal Jade Palace di Kota Kediri - Clairine Jessica; Hedy Cornelli Indrani; Poppy Firtatwentyna Nilasari (Intra, 2019)
Family restaurants in Indonesia are serving Chinese food in general. Chinese restaurant is a favorite restaurant for Indonesian people. Because the portion of the food can be shared with one family. This Crystal Jade Palace restaurant is a family restaurant that serves Chinese food.There is still less family restaurant in Kediri that serves Chinese food. The existing Chinese food restaurant still doesn’t have attractive interior. Many people nowadays choose to eat in restaurants that have attractive interiors, which can be used as a place to take pictures.The Crystal Jade Palace restaurant was designed with an oriental comfort concept. Oriental means Chinese, while comfort means comfort like family. This design provides warmth, and comfort like family for its employees or restaurant visitors.